2022
DOI: 10.3390/jcm11216566
|View full text |Cite
|
Sign up to set email alerts
|

The Clinicopathological Distinction between Immune-Mediated Necrotizing Myopathy and Limb–Girdle Muscular Dystrophy R2: Key Points to Prevent Misdiagnosis

Abstract: Background: Limb–girdle muscular dystrophy R2 (LGMD R2) is most frequently misdiagnosed as immune-mediated necrotizing myopathy (IMNM). This study aimed to compare the clinicopathological data of IMNM and LGMD R2 to find distinguishing features. Methods: We retrospectively reassessed the medical data of patients with IMNM (n = 41) and LGMD R2 (n = 8) treated at Tongji Hospital from January 2017 to December 2021. Results: In our cohort, patients with LGMD R2 had a longer interval of onset to first visit, mild m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The radiomics features in each model were from calf, thigh and “calf + thigh” images, respectively. The difference in the distribution and severity of muscular fatty infiltration and atrophy between LGMDR2 and IMNM can be clearly shown in the T1-weighted sequence ( 5 ). Water-only images, including the water signal without fat interference, can exhibit edema of muscle and muscular fascia ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The radiomics features in each model were from calf, thigh and “calf + thigh” images, respectively. The difference in the distribution and severity of muscular fatty infiltration and atrophy between LGMDR2 and IMNM can be clearly shown in the T1-weighted sequence ( 5 ). Water-only images, including the water signal without fat interference, can exhibit edema of muscle and muscular fascia ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on using the Mercuri scale based on the T1-weighted sequence to identify the different patterns of myopathies suggested that this visual scoring could be advantageous in conveniently applied in clinical practice, especially in primary care hospitals ( 8 , 31 ). Some studies reported selectively involved pattern characterization of muscles evaluated by the Mercuri scale in LGMDR2 and IMNM patients ( 8 , 9 ) and compared the distributions and characteristics of intramuscular fatty infiltration of lower limbs between these two diseases ( 5 ). However, different muscular disorders may have various patterns and degrees of muscular fatty infiltration, edema or atrophy ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations